The Influence of Organizational Support and Job Satisfaction on Organizational Citizenship Behavior with Organizational Commitment as an Intervening: A Study on CV Baby Cloudfoam - Yurisnawati, Septieya; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of organizational support and job satisfaction on organizational citizenship behavior using organizational commitment interventions. The sample for this research consisted of 40 respondents who were CV employees. Dear Cloudfoam. The data collection technique used is a survey method using a research instrument in the form of a questionnaire. The variables used in this research are organizational support, satisfaction, organizational commitment and organizational citizenship. and organizational citizenship behavior. The outcome of this research provide confirmation for the CV. Cloudfoam Baby is designed to further increase organizational support and job satisfaction for organizational citizenship behavior as well as organizational support for organizational commitment so that it can influence organizational citizenship behavior and organizational commitment.